2017
DOI: 10.1177/2050640617722310
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vedolizumab for induction of clinical response and remission in patients with moderate to severe inflammatory bowel disease who failed at least two TNF antagonists

Abstract: Up to 70% TNF-refractory/intolerant UC and CD patients achieved a clinical response after 10 to 14 weeks of vedolizumab treatment in this real-life cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
13
2
1
Order By: Relevance
“…2,3 Although the efficacy and safety of VDZ induction and maintenance therapy in CD has been confirmed in real-life cohorts, only limited data are available on endoscopic and histological remission. [4][5][6][7][8] Endoscopic remission is an important treatment goal in CD that is associated with improved clinical outcomes, including reduced hospitalization and surgery rates. 9,10 Moreover, endoscopic response is recommended as a co-primary endpoint in clinical trials by regulatory agencies.…”
Section: Background and Aimsmentioning
confidence: 99%
“…2,3 Although the efficacy and safety of VDZ induction and maintenance therapy in CD has been confirmed in real-life cohorts, only limited data are available on endoscopic and histological remission. [4][5][6][7][8] Endoscopic remission is an important treatment goal in CD that is associated with improved clinical outcomes, including reduced hospitalization and surgery rates. 9,10 Moreover, endoscopic response is recommended as a co-primary endpoint in clinical trials by regulatory agencies.…”
Section: Background and Aimsmentioning
confidence: 99%
“…The pivotal large-scale GEMINI clinical trials have demonstrated safety and efficacy of vedolizumab in both CD and UC with clinical remission rates of 39% and 42% maintained at 12 months [15,16]. Vedolizumab is effective in the treatment of anti-TNF naive and anti-TNF failure patients and benefits may continue long-term regardless of exposure status [17][18][19]. However, anti-TNF naive CD patients tend to respond better than those with previous exposure [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the highly selective character of trial enrollment, it is always fundamental to observe whether real‐life settings support the initially reported results of a new drug . Real‐world publications on this field are accumulating, with some conflicting results, but only a few of them include long‐term evaluation at 1 year with endoscopic assessment . Therefore, we presented an Italian single‐center study on VDZ long‐standing effectiveness and tolerability in patients with UC and CD at a tertiary referral setting.…”
Section: Introductionmentioning
confidence: 99%